2017
DOI: 10.1097/icu.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis after cataract surgery

Abstract: Endophthalmitis prevention is at an interesting crossroad. Although there is hesitation the intracameral injection of antibiotics is increasingly being adopted by physicians, which is likely to grow further with commercial availability of formulations. However, it will be important to be cautious and report all adverse reactions associated with this practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Numerous recent review articles have discussed in detail the evidence towards and against routine use of IC antibiotic prophylaxis. [ 57 58 59 60 ] We agree with the 2016 American Academy of Ophthalmology Cataract Preferred Practice Pattern's assessment of the published literature that “there is mounting evidence that injecting IC antibiotics as a bolus at the conclusion of surgery is an efficacious method of endophthalmitis prophylaxis.”[ 61 ] There is much stronger evidence supporting the efficacy of IC antibiotic injection than for topical administration for endophthalmitis prophylaxis.…”
Section: Discussionmentioning
confidence: 72%
“…Numerous recent review articles have discussed in detail the evidence towards and against routine use of IC antibiotic prophylaxis. [ 57 58 59 60 ] We agree with the 2016 American Academy of Ophthalmology Cataract Preferred Practice Pattern's assessment of the published literature that “there is mounting evidence that injecting IC antibiotics as a bolus at the conclusion of surgery is an efficacious method of endophthalmitis prophylaxis.”[ 61 ] There is much stronger evidence supporting the efficacy of IC antibiotic injection than for topical administration for endophthalmitis prophylaxis.…”
Section: Discussionmentioning
confidence: 72%
“…Endophthalmitis is associated with a variety of factors, including the species and quantity of bacteria entering the anterior chamber, operative technique, sanitary condition, perioperative aseptic measures, and postoperative patient education. 43 Studies have reported intracameral antibiotics present no benefits when topical antibiotics are used, 3 or vice versa. 44 Lack of consensus makes it unlikely to conclusively define the optimal endophthalmitis prophylaxis techniques via additional clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Some ophthalmologists use pre- or postoperative topical antibiotics. 12 The drug itself, or other components of the drug solution, could potentially induce toxic side effects to the ocular surface cells. As discussed in more detail by Mantelli et al, 13 the detrimental role of topical therapies on the ocular surface and the thin border between their therapeutic and toxic effects may arise from both the preservatives and other components in the preparations depending on dose, frequency, and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%